If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 10 = 4x + 14 Reorder the terms: 10 + 5x = 4x + 14 Reorder the terms: 10 + 5x = 14 + 4x Solving 10 + 5x = 14 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 5x + -4x = 14 + 4x + -4x Combine like terms: 5x + -4x = 1x 10 + 1x = 14 + 4x + -4x Combine like terms: 4x + -4x = 0 10 + 1x = 14 + 0 10 + 1x = 14 Add '-10' to each side of the equation. 10 + -10 + 1x = 14 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 14 + -10 1x = 14 + -10 Combine like terms: 14 + -10 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| LM=3x+8 | | 42+2y=9y | | X^3-2-3x+2=0 | | 3x(x-3)-(x+1)(3x+2)=8 | | 2x+40=128 | | 16x^2+24+9=0 | | 2x-50=138 | | 2(1-5v)= | | f(x)=3x^2+12x+1 | | T=DC-3 | | f(x)=3x^2+x+1 | | 6x+7=4x+37 | | 13-6x=x+27 | | 7x-28=10x-13 | | y^2-5y-27=9 | | 5x-4y-4x+6y=0 | | -2=(1/(1+x))-(3/(1-x)) | | -7+1/4z=0 | | 4x+36=12x^60 | | 5-y=10-2y | | X-2=2x-12 | | -11(2x-5)=0 | | 2x-62=106 | | x=7x-154+33+(11*11) | | 0=(4y-y^2)/(y^2-4) | | 4x+36=12x/60 | | 2x-22=114 | | 4(6-w)=3(2w+2) | | 5+3m=5m-19 | | 231-4x=41x+21 | | 6(2x-4)-3x=15 | | y=3x^2+42x-56 |